PENGARUH KEYAKINAN DAN KEPERCAYAAN TEKNOLOGI TERHADAP MINAT PENGGUNAAN INTERNET BANKING DI SURABAYA - Jocelyn Gunawaty; Siti Rahayu; Veny Megawati (Perpustakaan Universitas Surabaya, 2020)
This study was conducted to analyze the influence between self efficacy and trust in technology on the intention to use internet banking. The result of this study accepted all hypothesis and consistent with Mardiyanti (2014) research and another researchs that analyzed the same thing. This proves that there is influence between trust and efficacy on technology and the intention on using internet banking. This research also can be use for banking as considerations to choose the SST alternative that will be provided for customer and drive customer to use SST especially for internet banking based on the result of this study.